Modelos de spins geometricamente frustrados: transição de fase e estruturas de platores - Litaiff, Fabian Cardoso (Universidade Federal de São Carlos, 2013)
This thesis presents a study of the magnetization plateau and the phenomenon of geometrical frustration in spin systems applied to lattices with triangular structure, as well as the results achieved by applying the differential operator technique of the Ising and Heisenberg models with external magnetic field applied to the easy magnetization axis z, their phase diagrams, behavior plateaus observed and analyzed according to the Haldane conjecture and appearance of plateaus presented by Oshikawa, Yamanaka and Affleck, and also to study the behavior of the magnetic susceptibility in order to verify the behavior of frustrated systems using the frustration factor f= θWC/TN to verify frustration encountered at various stages of the study models
Keywords: Magnetismo; Platô; Operadores diferenciais; Transição de fase; Ising, Modelo de; Modelo de Heisenberg; Diagramas de fase; Fator de frustração; Magnetization plateaus; Phase diagrams; Frustration factor; Differential operator; Ising model; Heisenberg model; CIENCIAS EXATAS E DA TERRA::FISICA